(untitled) (Editora Impacto Científico, 2025)
Palliative care aims to improve the quality of life of patients with advanced chronic illnesses and their families by alleviating suffering in its multiple dimensions: physical, psychological, social, and spiritual. This study aimed to analyze the role of nurses within the context of palliative care. It was an integrative literature review, carried out through a bibliographic survey in the following databases: Virtual Health Library (BVS-BIREME), Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), and Nursing Database (BDENF), using the Health Sciences Descriptors (DeCS): “Palliative Care,” “Nursing Care,” “Nursing,” and the Boolean operator “AND.” Eligibility criteria included: articles published between 2020 and 2024, available in full text and electronically accessible in Portuguese. The findings highlight the strategic role of nurses in promoting comfort, managing pain, and providing humanized care, encompassing clinical interventions and emotional support for patients and their families. The main challenges identified include gaps in professional training, lack of specific protocols, and the emotional toll of caregiving. It is concluded that continuous training in palliative care is essential to ensure safe, ethical, and dignity-centered nursing practices. DOI: https://doi.org/10.56238/edimpacto2025.090-048